RELIGIOUS ACTIVITIES OF THE CHAM PEOPLE IN HO CHI MINH CITY, VIETNAM (International Conference on Social and Islamic Studies, 2021)
The Cham ethnic group was one of the first to settle in Saigon - Ho Chi Minh City. The Cham community in Ho Chi Minh City has formed a distinct identity despite the factthat the population distribution is far from the original community and, at the sametime, under the influence and influence of many other cultural flows. The local character contributes to the diversity and richness of Ho Chi Minh City's cultural and human characteristics. Economic activities, social organization, and religious activities are the most visible manifestations of this cultural feature. The process of forming the Cham community in Ho Chi Minh City, as well as the characteristics of their religious activities, are discussed in this article.